RELATIONSHIP OF POST TRAUMATIC GROWTH PSYCHOLOGICAL DISTRESS AND QUALITY OF LIFE AMONG RENAL FALIURE PATIENTS - Neelam Ehsan (Army Medical College Rawalpindi, 2021)
Objective: To study the relationship and impact of post traumatic growth and psychological distress on quality of life among renal failure patients seeking dialysis, and to see differences in these variables among different age group patients.